(untitled) - Huỳnh, Thị Tường Vy (Cần Thơ, 2020)
The use of English as a Medium of Instruction (EMI) has become a great trend in many universities, especially EFL universities all over the world in this globalization era. However, teachers of some developing countries still have challenges dealing with the influences and preparations of using EMI in their own tertiary contexts. This investigation aims to get insights into content teachers’ perceptions of using EMI in a university in the Mekong Delta, Vietnam. The mixed methods approach was conducted to analyze both quantitative instrument with 64 content teachers and qualitative instruments with 9 content teachers. The findings revealed a current situation that although the university had already released the piloting EMI language policy for years, content teachers still just applied it to a limited extent. Participants all agreed with the influences of EMI but emphasized the difficulties toward the limitations of students’ English proficiency and content teachers’ readiness of EMI implementation. Finally, respondents also claimed the cooperation of university and content teachers in designing and piloting an EMI curriculum at a faculty before implementing it officially to other faculties in the school.
Keywords: Anh ngữ,English language; Học và dạy học,Study and teaching